Terahertz Spectroscopy of Novel Superconductors - Stefano Lupi (Advances in Condensed Matter Physics)
Through the coupling of Synchrotron Radiation and Michelson interferometry, one may obtain in the terahertz (THz) range transmittance and reflectivity spectra with a signal-to-noise ratio (S/N) up to 103. In this paper we review the application of this spectroscopic technique to novel superconductors with an increasing degree of complexity: the single-gap boron-doped diamond; the isotropic multiband V3Si, where superconductivity opens two gaps at the Fermi energy; the CaAlSi superconductor, isostructural to MgB2, with a single gap in the hexagonal ab plane and two gaps along the orthogonal c axis.